Ներսես Շնորհալի և Կոմիտաս վարդապետ - Սահակյան, Լուսինե
The article presents the relationship between Nerses Shnorhali and Komitas Vardapet, which are of import not only the study of Komitas and medieval musical traditions, but also to the study of music and ethnomusicology writ large. Komitas Vardapet dealt with the legacy of Nerses Shnorhali both in his musical and educational pursuits. On May 28, 1893, Komitas presented his graduate thesis entitled “Shnorhali: his Era and the Religious Problems of his Time” to the Gevorgyan Seminary Board of Education. In this study he addresses the life and activities of the Catholicos, covering a number of historical, political and religious issues. This work was the starting point of Komitas’ lifelong engagement with the work and musical legacy of Shnorhali. From his very first article treating Armenian Church music, Komitas Vardapet emphasized the ideas and findings of Nerses Shnorhali, as well as the tonal and metrical features of Shnorhali’s musical and poetic art. Komitas highly appreciated the traditions of the Cilician school and sought to analyse and define the method of Armenian manrusumn (melismatic chants of the Breviary). In Komitas’s recordings of spiritual music, the hymns and chants of Nerses Shnorhali occupy a key place. They are not abundant, but they are of exceptional artistic value. At the same time, Komitas Vardapet's recordings are distinguished by their artistic merit, and their sensitivity to Shnorhali’s style. Komitas Vardapet sang the hymns of Nerses Shnorhali both in church and in concert performance. В статье рассматривается отношение Комитаса Вардапета к творчеству Нерсеса Шнорали. Данный вопрос имеет ключевое значение не только для комитасоведения и музыкальной медиевистики; он представляет интерес и в общем контексте всей мировой музыкальной культуры. Наследием Шнорали Комитас занимался на протяжении всей своей музыкально-просветительской деятельности. 28 мая 1893 года на суд учебного совета духовной семинарии Геворгян Комитас представил свою выпускную работу под названием «Шнорали. Его эпоха и волнующие его религиозные вопросы того времени», которое было удостоено премии. В исследовании Комитас осветил ряд вопросов, касающихся историко-политических и религиозных аспектов жизни и деятельности католикоса. Оно стало отправной точкой для глубокого познания творчества Шнорали, профессионального изучения его музыкального наследия. В первой же статье, посвященной армянской церковной музыке, Комитас Вардапет подчеркнул особую роль Нерсеса Шнорали в ее развитии, высоко оценил его мысли и суждения, обратил внимание как на стиховые, так и на ладовые особенности его музыкально-поэтического искусства. Характеризуя мелодические образцы «манрусума» (мелизматических песен Часослова), Комитас очень высоко оценил заслуги Киликийской школы. В комитасовских записях духовной музыки особо важное место занимают шараканы и священные песнопения Нерсеса Шнорали. И, хотя их количество невелико, они представляют исключительную художественную ценность. При этом записи Комитаса Вардапета отличаются совершенством поэтического и музыкального языка, тончайшим чувством стиля Шнорали. Произведения Нерсеса Шнорали в исполнении Комитаса звучали как в церкви, так и в концертном исполнении.
Keywords: Եկեղեցական երաժշտություն; Հոգևոր ժառանգություն